2017
DOI: 10.1039/c7cc06248f
|View full text |Cite|
|
Sign up to set email alerts
|

Exploiting electronic strategies to stabilize a planar tetracoordinate carbon in cyclic aromatic hydrocarbons

Abstract: A new approach to stabilize compounds containing a planar tetracoordinate carbon (ptC), embedded in aromatic hydrocarbons, is presented herein. This is achieved by using ligands that promote the formation of a 3c-2e σ-bond with the ptC under two conditions: without altering the sp hybridization of the aromatic carbons; and containing empty orbitals perpendicular to the aromatic ring to participate in the aromatic π-electronic delocalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
52
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 38 publications
5
52
0
Order By: Relevance
“…The concept of molecules with a planar tetracoordinate carbon (ptC) 1,2 atom is an inspiration to all chemists despite it breaks one of the fundamental paradigms of organic chemistry -i.e., tetrahedral tetracoordinate carbon. [3][4][5][6][7][8][9][10][11][12][13][14] Experimental and theoretical confirmation of pentaatomic ptC species (CAl − 4 , CAl 3 Si −/0 , CAl 3 Ge −/0 , CAl 2− 4 , etc.,) [15][16][17][18] have given some momentum in the search of these molecules in the gas phase. Stabilization of ptC by hydrogenation, in the case of CAl 4 H −/0 , has also been reported recently.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of molecules with a planar tetracoordinate carbon (ptC) 1,2 atom is an inspiration to all chemists despite it breaks one of the fundamental paradigms of organic chemistry -i.e., tetrahedral tetracoordinate carbon. [3][4][5][6][7][8][9][10][11][12][13][14] Experimental and theoretical confirmation of pentaatomic ptC species (CAl − 4 , CAl 3 Si −/0 , CAl 3 Ge −/0 , CAl 2− 4 , etc.,) [15][16][17][18] have given some momentum in the search of these molecules in the gas phase. Stabilization of ptC by hydrogenation, in the case of CAl 4 H −/0 , has also been reported recently.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of molecules with a planar tetracoordinate carbon (ptC) [ 1,2 ] atom is an inspiration to all chemists [ 3–15 ] despite it breaking one of the fundamental paradigms of organic chemistry—that is, tetrahedral tetracoordinate carbon. [ 16,17 ] Experimental and theoretical confirmation of pentaatomic ptC species (CAl4, CAl 3 Si −/0 , CAl 3 Ge −/0 , CAl42, etc.,) [ 18–21 ] has provided some momentum in the search of these molecules in the gas phase.…”
Section: Introductionmentioning
confidence: 99%
“…A vast number of molecules with a ptC have been designed using such an approach. [21][22][23][24][25][26][27][28][29][30][31][32][33] Quite recently, we suggested an alternative to stabilize a ptC compound by localizing π-orbitals between the central carbon and a ligand in the CEM3 compounds. The formation of a double C=E bond can compensate for the weakening of C-M and ligand-ligand interactions (see right side of Fig.…”
Section: The Exhaustive Exploration Of the Potential Energy Surfaces mentioning
confidence: 99%
“…5 On the other hand, in the mechanical approach, a central planar tetracoordinated carbon atom is structurally constrained by forming a cage around it. [15][16][17][18][19][20][21] Wong and Radom 22 showed that the planar form of methane dication is a minimum but does not exhibit a square shape and about a decade later Wang and Schleyer 23 found similar planar form of methane dication that lacks the lone pair in the central atom to be a minimum on its potential energy surface (PES) and proposed this to be an alternative model based on which a large number of species have been designed. Recently, two hydrogenated ptC species, CAl 4 H and CAl 4 H − were identified based on a photoelectron spectroscopic and quantum chemical study.…”
Section: Introductionmentioning
confidence: 99%